The state of TRUS biopsy sepsis: readmissions to Victorian hospitals with TRUS biopsy‐related infection over 5 years. (October 2015) - Roth, Hedley; Millar, Jeremy L; Cheng, Allen C; Byrne, Amanda; Evans, Sue; Grummet, Jeremy
Abstract : Objectives: To describe the incidence, morbidity and mortality of men who developed infectious complications requiring hospital admission following TRUS prostate biopsy in Victoria, Australia. Further it aimed to report the financial cost of these admissions. Subjects & Methods: The Department of Health's Victorian Admitted Episodes Data Set was used to identify those patients who underwent TRUS biopsy in Victoria who were subsequently readmitted within 7 days to any Victorian hospital with infective complications from July 2007 to June 2012. All Victorian public and private hospitals were included. Patients were excluded if their biopsy was performed during a multi‐day admission. Financial costing data was obtained where available from the Department Of Health and Human Services for readmissions with post‐TRUS infection where available and adjusted to 2012 prices. Institutional ethics committee approval was granted for this study. Results: Thirty‐four thousand eight hundred and sixty‐five TRUS biopsies were performed in the 5‐year period. 1276 (3.66%) were readmitted to a Victorian hospital within 7 days. 604 (1.73%) of these were readmitted with a biopsy‐related infection. No significant trend in sepsis rates was seen in 5 years. The median readmission LOS was 4 days. The total burden of readmissions was 3 686 days over 5 years. One patient readmitted with a biopsy related infection died during that episode of care. 20 051 (57.51%) of biopsies resulted in a diagnosis of prostate cancer. Financial costing data was available for 218 (36%) of infectious readmissions with a mean cost per readmission were $7 362 AUD (£4137 or $6844 USD, 95% CI $6219–8505 AUD) or $1 256 AUD per day. Conclusion: Infection following TRUS biopsy was associated with a readmission rate for infection of 1 in 57 biopsies, an excess of 3 686 bed days required over 5 years with a cost of $1 256 AUD per day. The rate of infection remained stable for the period examined.